Macroeconomic Impact of Basel III: Evidence from a Meta-Analysis - Jarko Fidrmuc; Ronja Lind (Verein für Socialpolitik, Ausschuss für Wirtschaftssysteme und Institutionenökonomik, 2017)
We present a meta-analysis of the impact of higher capital requirements imposed by regulatory reforms on the macroeconomic activity (Basel III). The empirical evidence derived from a unique dataset of 48 primary studies indicates that there is a negative, albeit moderate GDP level effect in response to a change in the capital ratio. Meta-regression results suggest that the estimates reported in the literature tend to be systematically influenced by a selected set of study characteristics, such as econometric specifications, the authors' affiliations, and the underlying financial system. Finally, we document a significant positive publication bias.
Keywords: E51; E44; G28; 330; Meta-analysis; publication bias; banking; loans; capital requirements; Basel III